Laying the foundations for hepatitis C elimination: evaluating the development and contribution of community care pathways to diagnostic efforts - Emma Robinson; Christopher J. Byrne; James Carberry; Andrew Radley; Lewis J. Beer; Sarah K. Inglis; Jan Tait; Iain Macpherson; David Goldberg; Sharon J. Hutchinson; Matthew Hickman; John F. Dillon (BMC, 2023)
Abstract Background Hepatitis C Virus (HCV) is a public health threat which contributes substantially to the global burden of liver disease. There is much debate about effective approaches to scaling up diagnosis of HCV among risk groups. Tayside, a region in the East of Scotland, developed low-threshold community pathways for HCV to lay the foundations of an elimination strategy. In this retrospective study, we sought to: quantify the contribution of community pathways to increasing HCV diagnosis; understand if shifting diagnosis to community settings led to a higher proportion of individuals tested for HCV being actively infected; and describe functional characteristics of the care pathways. Methods Descriptive statistics were used to for analysis of routinely-collected HCV testing data from 1999 to 2017, and a review of the development of the care pathways was undertaken. Community-based testing was offered through general practices (GP); nurse outreach clinics; prisons; drug treatment services; needle and syringe provision (NSP) sites; community pharmacies; and mosques. Results Anti-HCV screening was undertaken on 109,430 samples, of which 5176 (4.7%) were reactive. Of all samples, 77,885 (71.2%) were taken in secondary care; 25,044 (22.9%) in GPs; 2970 (2.7%) in prisons; 2415 (2.2%) in drug services; 753 (0.7%) in NSPs; 193 (0.2%) pharmacies; and 170 (0.1%) in mosques. The highest prevalence of HCV infection among those tested was in NSP sites (26%), prisons (14%), and drug treatment centres (12%). Conclusions Decentralised care pathways, particularly in harm reduction and other drug service settings, were key to increasing diagnosis of HCV in the region, but primary and secondary care remain central to elimination efforts.